Application of multiple-path particle dosimetry (MPPD) model in aged-specify schoolchildren airways exposed to ambient particulate matter in Malaysia - Junaidi, Ernie Syazween; Jalaludin, Juliana; Latif, Mohd Talib (Taylor and Francis, 2025)
Exposure to particulate matter (PM) significantly cause adverse health effects in children, particularly respiratory health issues from inhalation through nose or mouth followed by deposition in the respiratory system. This study investigated PM2.5 and PM10 deposition in children’s lungs in selected areas of Malaysia from 2018 to 2020. The Multiple-Path Particle Dosimetry (MPPD) model Ver. 3.04 was utilized for quantifying PM deposition and clearance rates. Airway structures of children (8- and 9-year) and 21-year were modeled to compare primary school-aged children and adult. The findings revealed that 73–76% of inhaled PM2.5 and 96–99% of PM10 were deposited, with the highest deposition in adults. However, children had higher PM deposition in specific lung regions due to physiological and anatomical factors. In the tracheobronchial (TB) region, 9-year group had the highest PM10 deposition (30%), while PM2.5 was highest in the pulmonary region of 8-year group (40%). Lobar deposition patterns varied, with 8-year group showing higher PM2.5 levels in the left lower (14%) and right upper (9%) lobes, whereas 9-year group had elevated levels in the left upper (7%) and right lower (15%) lobes. Children had greater size-segregated deposited fractions and mass compared to adults, indicating heightened vulnerability. The clearance rate of deposited PM was higher in the TB region and lower in the pulmonary region. This study concludes PM as a critical pollutant affecting children’s lung health more severely than adults. Further, the present results will be beneficial for children health risk assessments, such as oxidative potential and toxicity of deposited PM.